2012
DOI: 10.1007/s00467-012-2322-6
|View full text |Cite
|
Sign up to set email alerts
|

Home haemodialysis

Abstract: Haemodialysis (HD) began as an intensive care treatment offered to a very select number of patients in an attempt to keep them alive. Outcomes were extremely poor, and the procedure was cumbersome and labor intensive. With increasing expertise and advances in dialysis equipment, HD is now recognised as a life-sustaining treatment that is considered a standard of care for children with end stage renal disease (ESRD). Assessment of efficacy has evolved from mere survival, through achieving minimal standards of "… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 27 publications
0
16
0
1
Order By: Relevance
“…Home visits to review children on CPD has a proven advantage in detecting and anticipating poor practice that might lead to complications such as peritonitis [39]. Increasing interest in home haemodialysis certainly necessitates robust home support mechanisms [40].…”
Section: Delivery Of Psychosocial Carementioning
confidence: 99%
“…Home visits to review children on CPD has a proven advantage in detecting and anticipating poor practice that might lead to complications such as peritonitis [39]. Increasing interest in home haemodialysis certainly necessitates robust home support mechanisms [40].…”
Section: Delivery Of Psychosocial Carementioning
confidence: 99%
“…One study in children demonstrated an improvement in the risk for hospitalization up to a Kt/V of Pediatric Nephrology DOI 10.1007/978-3-642-27843-3_63-1 # Springer-Verlag Berlin Heidelberg 2015 that level, but above 1.4, no further improvement occurred [48]. However, the improvement in all aspects of patient well-being with daily or frequent short hemodialysis suggests that a higher Kt/V must be better [12,[16][17][18][19][20][21][22][23].…”
Section: Dialysis Adequacymentioning
confidence: 87%
“…However, attainment of optimum weight with conventional three times a week dialysis can be difficult in the child who has high interdialytic weight gains requiring large UF volumes. Much better results have been obtained with daily dialysis, with most children no longer needing antihypertensives at all [12].…”
Section: Estimation Of Optimum Weight and Fluid Removalmentioning
confidence: 92%
See 2 more Smart Citations